2021
DOI: 10.1093/bjsopen/zrab116
|View full text |Cite
|
Sign up to set email alerts
|

Negative-pressure wound therapy after stoma reversal in colorectal surgery: a randomized controlled trial

Abstract: Background Stoma-reversal surgery is associated with high postoperative morbidity, including wound complications and surgical-site infections (SSIs). This study aims to assess whether the application of negative-pressure wound therapy (NPWT) can improve wound healing compared with conventional wound dressing. Methods This was a single-centre, superiority, open-label, parallel, individually randomized controlled trial. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Some of the most common surgical procedures that patients underwent were low anterior resection, colectomy and abdominoperineal resection (see Table 2). Most interventions were delivered in academic (Arslan et al., 2020; Chadi et al., 2014; Cima et al., 2013; Curchod et al., 2022; Curran et al., 2019; Forsmo et al., 2016; Han et al., 2021; Keenan et al., 2014, 2015; Martinez et al., 2020; Pan et al., 2015; Park et al., 2020; Poehnert et al., 2017; Tanner et al., 2016; Wierdak et al., 2021) and tertiary facilities (Carrano et al., 2021; Chadi et al., 2014; Cima et al., 2013; D'Souza et al., 2019; Keenan et al., 2014, 2015; Martinez et al., 2020; Ocaña Jiménez et al., 2019; Park et al., 2020; Poehnert et al., 2017; Wierdak et al., 2021). The units where interventions/quality improvement initiatives were delivered were surgical (Hewitt et al., 2017; Pellino, Sciaudone, Candilio, de Fatico, et al., 2014; Selvaggi et al., 2014; Watanabe et al., 2017), colorectal (Gorgun et al., 2018; Pan et al., 2015; Shakeshaft et al., 2020), gastroenterology (Han et al., 2021) and general surgical units (Arslan et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the most common surgical procedures that patients underwent were low anterior resection, colectomy and abdominoperineal resection (see Table 2). Most interventions were delivered in academic (Arslan et al., 2020; Chadi et al., 2014; Cima et al., 2013; Curchod et al., 2022; Curran et al., 2019; Forsmo et al., 2016; Han et al., 2021; Keenan et al., 2014, 2015; Martinez et al., 2020; Pan et al., 2015; Park et al., 2020; Poehnert et al., 2017; Tanner et al., 2016; Wierdak et al., 2021) and tertiary facilities (Carrano et al., 2021; Chadi et al., 2014; Cima et al., 2013; D'Souza et al., 2019; Keenan et al., 2014, 2015; Martinez et al., 2020; Ocaña Jiménez et al., 2019; Park et al., 2020; Poehnert et al., 2017; Wierdak et al., 2021). The units where interventions/quality improvement initiatives were delivered were surgical (Hewitt et al., 2017; Pellino, Sciaudone, Candilio, de Fatico, et al., 2014; Selvaggi et al., 2014; Watanabe et al., 2017), colorectal (Gorgun et al., 2018; Pan et al., 2015; Shakeshaft et al., 2020), gastroenterology (Han et al., 2021) and general surgical units (Arslan et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent interventions/quality improvement initiatives were negative pressure wound pressure therapy (NWPT) (Abadía et al., 2021; Borejsza‐Wysocki et al., 2021; Carrano et al., 2021; Chadi et al., 2014; Curchod et al., 2022; Curran et al., 2019; León Arellano et al., 2021; Murphy et al., 2019; Ocaña Jiménez et al., 2019; Okuya et al., 2020; Pellino, Sciaudone, Candilio, Campitiello, et al., 2014; Pellino, Sciaudone, Candilio, de Fatico, et al., 2014; Poehnert et al., 2017; Selvaggi et al., 2014; Uchino et al., 2016; Webb et al., 2019; Wierdak et al., 2021) and SSI bundles (Cima et al., 2013; D'Souza et al., 2019; Gorgun et al., 2018; Hewitt et al., 2017; Keenan et al., 2014, 2015; Martinez et al., 2020; Park et al., 2020; Reese et al., 2020; Tanner et al., 2016). We found no interventions/quality improvement initiatives with nursing activities exclusively occurring in the postoperative phase; activities also occurred in the pre‐ and intraoperative phases, and all interventions/quality improvement initiatives had multidisciplinary input (see Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uchino et al also noted no difference in the efficacy rates between the use of NPWT and pursestring suture methods in preventing SSI [21]. Similarly, Carrano et al reported similar incidence rates of SSI and wound complications in both the NPWT and conventional dressing cohorts [22]. In contrast, the trial conducted by Wierdak et al reported a positive benefit in the use of prophylactic NPWT in the setting of ileostomy closure, with a reduced incidence of SSI and wound healing complications.…”
Section: Discussionmentioning
confidence: 99%
“…Terapia podciśnieniowa jest stosowana także w licznych zabiegach chirurgii jamy brzusznej. W przypadku operacji odwrócenia stomii grupa badanych u których zastosowano NPWT wykazała lepsze gojenie się ran, mniejszy ból i większe zadowolenie z estetyki niż grupa u której stosowano inne metody opatrywania rany [10] . Z kolei w pierwotnym zamknięciu powięzi na otwartym brzuchu bez urazu, NPWT w porównaniu do innej metodyworka Bogota -nie okazała się być metodą bardziej innowacyjną [11].…”
Section: Npwt W Leczeniu Owrzodzeń Stopy Cukrzycowejunclassified